On the Behavior of a Bolt–Nut Joint with Plastically Deformed Thread - Malinowski, J. Z.; Ostapkowicz, J. (Engineering Transactions, 2001)
The results of investigations connected with influence of tightening bolts above their yield stress on the fatigue life and loosening of the bolt-nut joints are presented. From numerical approach by the FEM, the dependence of the load distribution at the threads and maximal value of stress at the roots of thread on the tightening level of bolts is determined. The obtained results indicate, that tightening of a joint above its yield stress gives more uniform load distribution at the bolt thread, and stress distribution at the roots in part of the bolt screwed with the nut. Experimental investigations of the fatigue life of the bolt-nut joint with the tightening of the bolts below and above their yield stress are presented. The results indicate that tightening above the yield stress considerably increases the fatigue life of the joint. Experimental test of creep in the fatigue process and introductory test on dynamic loosening of the joint have been carried out. It was stated that the phenomenon of creep during the fatigue has no greater influence on the joint, and that the resistance to loosening of the joint increases with tightening of the bolt above its yield stress.